Knowee
Questions
Features
Study Tools

show that u(n) = summation k=-inf to n delta(k) =summation k=0 to infinity delta(n-k)

Question

Show that u(n)=k=nδ(k)=k=0δ(nk) u(n) = \sum_{k=-\infty}^{n} \delta(k) = \sum_{k=0}^{\infty} \delta(n-k)

🧐 Not the exact question you are looking for?Go ask a question

Solution

The given equation is a mathematical representation in the field of signal processing. Here, u(n) represents the unit step function, and delta(k) represents the Dirac delta function. The Dirac delta function is a mathematical construct which is used extensively in signal processing and system analysis.

The unit step function, u(n), is defined as:

u(n) = 0 for n < 0 u(n) = 1 for n >= 0

The Dirac delta function, delta(k), is defined as:

delta(k) = 0 for k ≠ 0 delta(k) = 1 for k = 0

Now, let's prove the given equation:

u(n) = Σ (from k=-∞ to n) delta(k)

This summation will add up all the values of delta(k) from k=-∞ to n. Since delta(k) is only 1 at k=0 and 0 otherwise, the summation will be 1 for all n >= 0 (since we include k=0 in the summation) and 0 for n < 0. This is exactly the definition of the unit step function, u(n).

Now, let's prove the second part of the equation:

u(n) = Σ (from k=0 to ∞) delta(n-k)

This summation will add up all the values of delta(n-k) from k=0 to ∞. Since delta(n-k) is only 1 at n=k and 0 otherwise, the summation will be 1 for all n >= 0 (since we include n=k in the summation) and 0 for n < 0. This is again exactly the definition of the unit step function, u(n).

Therefore, we have shown that:

u(n) = Σ (from k=-∞ to n) delta(k) = Σ (from k=0 to ∞) delta(n-k)

This problem has been solved

Similar Questions

An LTI system has the relationship y[n] = ∑ 𝑥[𝑘]𝑔[𝑛 − 2𝑘]∞𝑘= −∞ , where g[n] = u[n] –u[n-4]. Determine y[n] if a) x[n] = δ[n-1], b) x[n] = δ[n-2].

Derive the relationship between ∆ Ur and∆ Hr for reactions involving gaseousreactants and/or products

For endothermic reaction ans. ΔH is negative ΔU is negative ΔH is positive ΔH = 0

For endothermic reaction ans. ΔH is negative ΔH is positive ΔH = 0 ΔU is negative

By the integration by parts, we haveZ π−πf (x) cos(nx)dx = 1n f (x) sin(nx)π−π− 1nZ π−πf (x) sin(nx)dx

1/1

Upgrade your grade with Knowee

Get personalized homework help. Review tough concepts in more detail, or go deeper into your topic by exploring other relevant questions.